Organizational Archetypes of a Multi-National Company - Rutenberg, David P. (Management Science, 1970)
Decision premises, within which plans are made, should be formulated with an eye to the organization that will implement the results. This assertion seems especially relevant for multi-national companies which consist of a headquarters with subsidiaries around the globe. Four archetypes of the relationship between a headquarters and its subsidiaries are presented. These are based on theory developed by Leavitt (executive-workers), and Churchman and Schainblatt (analyst-manager). Each archetype is developed by using existing literature to explore patterns of bounded rationality that would emerge in different organizational structures. After an example of a corporation illustrative of the archetype, appropriate planning guidelines are presented for investment discount rates, pricing policy, product design, planned managerial rotation, and liquid asset management.